Renal artery stenosis: the challenging in diagnosis and therapy - Dewi, Ivana P.; Dewi, Kristin P.; Mardiana, N. (Ukrainian Journal of Nephrology and Dialysis, 2020)
Hypertension is still the most prevalent non-communicable diseases in Indonesia. Renovascular hypertension is one type of secondary hypertension. It is commonly caused by the presence of renal artery stenosis (RAS). Whereas, atherosclerosis (ARAS) and fibromuscular disease (FMD) are the most common causes of RAS. Early diagnosis is necessary because it has the potential to be cured by eliminating stenosis of the renal artery. However, the signs and symptoms of renovascular hypertension are not specific. The supporting examination to diagnose RAS is also expensive. So, screening in the population at risk is needed. The examinations to prove the presence of RAS are arteriography, captopril renogram, renal ultrasonography, renal Doppler ultrasonography, magnetic resonance angiography (MRA), and computed angiographic tomography (CTA). Until now, three therapeutic modalities can be selected in the management of renovascular hypertension; pharmacological therapy, surgical intervention, percutaneous intervention angioplasty with and without stenting. This narrative review summarizes the literature focused on the diagnosis and therapy of RAS.